Quantifying severe urinary complications after radical prostatectomy: the development and validation of a surgical performance indicator using hospital administrative data. (8th February 2017) - Sujenthiran, Arunan; Charman, Susan C.; Parry, Matthew; Nossiter, Julie; Aggarwal, Ajay; Dasgupta, Prokar; Payne, Heather; Clarke, Noel W.; Cathcart, Paul; van der Meulen, Jan
Abstract : Objectives: To develop and validate a surgical performance indicator based on severe urinary complications that require an intervention within 2 years of radical prostatectomy (RP), identified in hospital administrative data. Patients and Methods: Men who underwent RP between 2008 and 2012 in England were identified using hospital administrative data. A transparent coding framework based on procedure codes was developed to identify severe urinary complications which were grouped into 'stricture', 'incontinence' and 'other'. Their validity as a performance indicator was assessed by evaluating the consistency with diagnosis codes and association with patient and surgical characteristics. Kaplan–Meier methods were used to assess time to first occurrence and multivariable logistic regression was used to estimate adjusted odds ratios (ORs) for patient and surgical characteristics. Results: A total of 17 299 men were included, of whom 2695 (15.6%) experienced at least one severe urinary complication within 2 years. High proportions of men with a complication had relevant diagnosis codes: 86% for strictures and 93% for incontinence. Urinary complications were more common in men from poorer socio‐economic backgrounds (OR comparing lowest with highest quintile: 1.45; 95% confidence interval [CI] 1.26–1.67) and in those with prolonged length of hospital stay (OR 1.54, 95% CI 1.40–1.69), and were less common in men who underwent robot‐assisted surgery (OR 0.65, 95% CI 0.58–0.74). Conclusion: These results show that severe urinary complications identified in administrative data provide a medium‐term performance indicator after RP. They can be used for research assessing outcomes of treatment methods and for service evaluation comparing performance of prostate cancer surgery providers.